REPRESENTASI PERNIKAHAN DINI PERSPEKTIF: PRAMOEDYA ANANTA TOER - Wan Minto, Deri; Putriani, Ananda; Azwar, Rica; Indrayani, Teti; Ayunis (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The research was motivated by the phenomenon of early marriage which was criticized by Pramoedya Ananta Toer through a novel to the authorities